Performance Enhancement of Doubly Fed Induction Generator–Based Wind Farms With STATCOM in Faulty HVDC Grids - Pavan Kumar, Yellapragada Venkata; Kumar, Lagudu Venkata Suresh; Ananth, Duggirala Venkata Naga; Reddy, Challa Pradeep; Flah, Aymen; Kraiem, Habib; Al-Asad, Jawad F.; Kotb, Hossam; Aboras, Kareem M. (Frontiers in Energy Research, 2022)
In this study, an investigation of different faults for a wind turbine–based doubly fed induction generator (DFIG) system is studied and the performance using a static compensator (STATCOM) is observed. The DFIG network is connected to a voltage source converter high-voltage dc link with a fault occurring near the wind generator network. The ride through capability of DFIG is promising with STATCOM using the proposed control strategy. The ac and dc voltage and torque oscillations are damped effectively, and improved power flow is observed. The low voltage AC grid fault occurs for an HVDC transmission, and the DFIG performance without and with STATCOM is compared, where the DFIG converter control schemes are developed using the proposed improved field-oriented control (IFOC) method. In this, the reference rotor flux value alters to a new synchronous speed value or a slighter value or a standstill depending on the stator voltage dip due to grid disturbance. This speed variation leads to introducing rotor current at that new rotor slip frequency as there is a change in the rotor speed because of the fault, which further decreases the stator flux dc component. Hence, this dc-offset constituent in the stator flux is alleviated and decays rapidly in scheming the divergence of the speed of the rotor to a new orientation speed with decay in the rotor flux. This operation is done in the inner control scheme of the rotor converter, which is quicker in response to the faults. Apart from this, the stator’s real and reactive power also changes accordingly based on the lookup table mechanism–based closed-loop control action of the pulse generator, and this power change is done in the outer loop. The analysis for DFIG and HVDC operation is verified under different faults without and with STATCOM.